2010
DOI: 10.1007/s10517-010-0946-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopamine on Viability of BHK-21 Cells

Abstract: We studied the effects of dopamine added to culture medium on survival of floating or adherent BHK-21 cells differing by organization of actin cytoskeleton. The viability of floating cells more drastically decreased with increasing dopamine concentration and duration of exposure than that of adherent cells. The cells worse adhered to the substrate and formed a monolayer. The formed monolayer degrades, cell borders become blurred, cells, polygonal in the control, are rounded. Preliminary blockade of dopamine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…28 The mechanism of antioxidant effects of DA has not yet been examined in regard to DA interactions with lipid membranes. It is known that DA alters the cell ultrastructure and organization of actin cytoskeleton, 29,30 but, to our surprise, the only publication on DA/biomembrane interactions we have found was a molecular dynamics study assisted by a few measurements of surface pressure of lipid monolayer containing DA, a paper published very recently by Orłowski et al 31 Therefore, we decided to carry out a series of experiments in order to obtain thermodynamic description of DA/membrane interactions. According to our knowledge, this is the first experimental study in this field.…”
mentioning
confidence: 99%
“…28 The mechanism of antioxidant effects of DA has not yet been examined in regard to DA interactions with lipid membranes. It is known that DA alters the cell ultrastructure and organization of actin cytoskeleton, 29,30 but, to our surprise, the only publication on DA/biomembrane interactions we have found was a molecular dynamics study assisted by a few measurements of surface pressure of lipid monolayer containing DA, a paper published very recently by Orłowski et al 31 Therefore, we decided to carry out a series of experiments in order to obtain thermodynamic description of DA/membrane interactions. According to our knowledge, this is the first experimental study in this field.…”
mentioning
confidence: 99%
“…47 Dopamine also alters the cell ultrastructure and organization of the actin cytoskeleton of mammalian cells. 48,49 The precise PDA structure is not established; however, it is often presented as a catechol/ amine/quinone/indole heteropolymer or eumelanine-like oligoindoles. 47 This study confirmed that PDA-Zn@CuO completely inhibited the growth of E. coli as confirmed by an SEM micrograph obtained for this affected bacterium (Figure 5).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%